Comparison of the clinical performance of a hybrid Alba 4D and the AMC-4 locoregional hyperthermia systems - Akke Bakker; Remko Zweije; H. Petra Kok; Lukas J. A. Stalpers; G. Henrike Westerveld; Karel A. Hinnen; Geertjan van Tienhoven; M. Willemijn Kolff; Hans Crezee (International Journal of Hyperthermia)
Objective The in-house developed 70 MHz AMC-4 locoregional hyperthermia system has been in clinical use since 1984. This device was recently commercialized as the Alba 4D (Medlogix®, Rome, Italy), with a similar geometrical 4-waveguide design. At the time of this study a hybrid Alba 4D was installed at our center, which incorporated elements of the AMC-4. This study aims to compare clinical performance of both devices.Methods During one year after clinical acceptance of the hybrid Alba 4D, both devices were used for treatment delivery in patients scheduled for locoregional hyperthermia. Each patient started with the AMC-4, next sessions were allocated to either device. Possible differences between Alba 4D and AMC-4 sessions in power, achieved temperature T0, T10, T50, T90, T100, treatment time and complaints per session, were evaluated using linear mixed models (LMMs) for repeated measures with patient as random effect.Results From March 2018 to April 2019, eleven patients with cervical, pancreatic, vaginal carcinoma and uterine leiomyosarcoma received 27 locoregional hyperthermia sessions with the Alba 4D and 34 sessions with the AMC-4. Median number of sessions per patient was 5 (range 3–13). Treatment results for both devices were not significantly different: T50 was 40.5 ± 1.0 °C vs. 40.8 ± 0.7 °C, applied power was 500 ± 79 W vs. 526 ± 108 W, for the Alba 4D vs. AMC-4, respectively.Conclusion Results of the first patients treated with the hybrid Alba 4D demonstrated comparable clinical performance of the Alba 4D and AMC-4 locoregional hyperthermia systems, and both devices are expected to yield similar favorable clinical results.